Understanding Multilingualism in EFL Extensive Listening Class by Utilizing Schoology and Curated Materials: Why is it Important? - Farah Sukmawati Wahidah; Januarius Mujiyanto; Dwi Rukmini; Katharina Rustipa (Universitas Negeri Semarang, 2021)
Understanding multilingualism in teaching and learning extensive listening is very useful for both lecturer and student. In doing extensive listening, the lecturer should equalize the students’ understanding of the different English in the world because there are several Englishes in the world that have different in pronunciation, accent, and speed of speech in order to make them successful in doing extensive listening by utilizing Schoology to record students’ activities in extensive listening and curated materials. Then, the lecturer should consider the students’ background, which influenced their listening performance, especially in doing extensive listening by utilizing Schoology. Their ability to choose and understand the materials and use Schoology may differ from one to another. Not only that, students’ ability to use and access the given link and Schoology also impacts students whether they can show good performance in extensive listening or not. To minimize those problems, the lecturer should help students choose the appropriate materials and familiarize them with different Englishes and Schoology as the application used to record their extensive listening activities.